Analisis Yuridis Atas Praktek Pinjam Meminjam Uang Tanpa Jaminan di Kalangan Masyarakat Pasar Tradisional Horas Kota Pematang Siantar - trinitaty saragih (Universitas Harapan Medan, 2021)
The people at the Horas traditional market, Siantar Barat Sub-district, Pematang Sianar, re allowed to pay their loan by installment, and the loan is without collateral such as land certificate or other valuable devices. Some debtors usually do not pay off their installment to creditors. Loan agreement such as this will have a potential risk for money lenders, but it seems that they have never learned their lesson so that it is necessary for either the debtors or the creditors (money lenders) to get legal protection. The research used juridical empirical method through which the gathered data were analyzed descriptively and qualitatively. The loan agreement without any collateral in the people at Pematang Siantar is the same as used-up loan as it is specified in Article 1754 and Article 1765 of the Civil Code which is not contrary to Article 46, paragraph 1 of Law on Banking. If a debtor does not want or is not able to pay his debt after he has been warned, the creditor can file his complaint about a default to the court, based on Article 1243 of the Civil Code for compensation, interest, or cost. Request for debt relief or the length of term should have creditor’s approval. If the request for interest relief is rejected, a debtor can file it to the Court based on the request of “Wocker-ordinantie 1938”. A debtor who is charged with offensive criminal case can sue the creditor based on Article 335, paragraph 1 and Article 368 of the Penal Code if there is blackmailing in dunning. Special law which regulates the implementation of loan agreement between individuals should always pay attention to the balance in legal and economic position between a creditor and a debtor and not contrary to laws. A creditor should keep the balance in a loan agreement, and a debtor should consider the amount of money he will borrow by comparing it with the profit he will get from it.